Gender Representation in English for Foreign Language (EFL) Textbook in Indonesia - Julistiana, Risma; Solihati, Tri Agustini; Fauziyah, Siti Salamah (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2025)
Gender representation plays a significant role in shaping social norms and perception, especially in education. The study  examines whether gender is represented equally and how this representation aligns with the gender equality principles promoted by the Merdeka Curriculum. This study investigates gender representation in the English for Nusantara 7th-grade textbook, focusing on five dimensions: visual and textual gender visibility, topic dominance, occupational and leisure activities, and the use of gender-neutral language, based on Hamdan’s (2008) framework. The research found that the textbook offers a balanced gender representation in some aspects, while others still require improvement. Male characters were slightly more dominant in illustrations, while female characters led in topics and occupational mentions. The use of inclusive language was positively noted. The findings indicate a relatively balanced gender portrayal, yet subtle patterns of traditional bias remain. These insights contribute to the broader discourse on inclusive education and may guide curriculum developers, educators, and policymakers in improving the gender sensitivity of future textbooks and learning materials.